Hypertension Induced by Hypoxia‐Inducible Factor Prolyl Hydroxylase Inhibitors in Treating Anemia in Patients With Chronic Kidney Disease: A Mini‐Review - Wei Zhang; Yan Li; Ji‐Guang Wang (The Journal of Clinical Hypertension, 2024)
ABSTRACT Hypoxia‐inducible factor prolyl hydroxylase (HIF‐PH) inhibitors are a new class of agents for the treatment of anemia in chronic kidney disease (CKD). Unlike traditional treatments such as erythropoiesis‐stimulating agents (ESAs), HIF‐PH inhibitors are orally administered drugs and may increase endogenous erythropoietin and improve iron homeostasis. However, a significant concern is their possible side effect on blood pressure. The current mini‐review summarizes the data of 26 randomized controlled (placebo or ESAs) trials on six different HIF‐PH inhibitors with regard to their potential influence on blood pressure and hypertension in the management of anemia in CKD. Overall, the use of HIF‐PH inhibitors was associated with a higher risk of hypertension than placebo (pooled risk ratio 1.36, 95% confidence interval [CI] 1.16–1.59), but a lower risk of hypertension than ESA treatment (pooled risk ratio 0.92, 95% CI 0.86–0.98), especially in CKD patients not undergoing dialysis (pooled risk ratio 0.85, 95% CI 0.73–0.98). This review highlights the importance of blood pressure monitoring during the treatment of HIF‐PH inhibitors, especially out‐of‐office blood pressure measurement.